Longitudinal predictors of aerobic performance in adolescent soccer players - Valente-dos-Santos, J.; Coelho e Silva, M. J.; Duarte, J.; Figueiredo, A. J.; Liparotti, J. R.; Sherar, L. B.; Elferink-Gemser, M. T.; Malina, R. M. (Medicina, 2012)
Background. The importance of aerobic performance in youth soccer is well established. The aim of the present study was to evaluate the contributions of chronological age (CA), skeletal age (SA), body size, and training to the longitudinal development of aerobic performance in youth male soccer players aged 10 to 18 years.